'Felt security' as a means of facilitating imagery rescripting in psychosis: a clinical protocol and illustrative case study. (2020) - Newman-Taylor, Katherine
Abstract: People with psychosis do not have routine access to trauma-focused cognitive behavioural therapy (CBT) interventions such as imagery rescripting (IR), partly due to clinical caution. This case study describes the use of a simple imagery task designed to engender 'felt security', as a means of facilitating IR with a woman struggling with distressing memory intrusions, linked to her voices and paranoia. We assessed the impact of the felt security task, which was used before IR to enable Kip to engage in reprocessing of her trauma memories, and again after IR so that she would leave sessions feeling safe. The brief imagery task was effective in improving felt security before IR sessions. Felt security then reduced during IR, when distressing material was recalled and reprocessed, and increased again when the task was repeated. It is not yet clear whether trauma-focused interventions such as IR need to be routinely adapted for people with psychosis. In the event that individuals express concerns about IR, if the person's formulation indicates that high levels of arousal may trigger an exacerbation of voices, paranoia or risk, or where clinicians are otherwise concerned about interventions likely to increase emotional arousal in the short term, the felt security task may facilitate safe and effective reprocessing of trauma memories. This in turn may increase access to trauma-focused CBT for people with psychosis. Key learning aims: (1) To understand that people with psychosis need access to trauma-focused CBT. (2) To be familiar with a simple attachment-based imagery task designed to foster 'felt security'. (3) To learn that this task may facilitate imagery rescripting in people with psychosis.